2008
DOI: 10.2118/102715-pa
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of the Forchheimer Equation for Non-Darcy Flow in Porous Media

Abstract: The subject of non-Darcy flow in hydraulically fractured wells has generated intense debates recently. One aspect of the discussion concerns the inertia resistance factor, or the so-called beta factor, ␤, in the Forchheimer equation, and whether the beta factor ␤ of a proppant pack should be constant over the range of flow rates of practical interests. The problem was highlighted in a recent discussion by van Batenburg and Milton-Tayler (2005) and the reply by Barree and Conway (2005) regarding paper SPE 89325… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(66 citation statements)
references
References 61 publications
2
64
0
Order By: Relevance
“…3 does not apply at all flow velocities. In many studies (Fand et al 1987;Huang and Ayoub 2008;Seguin et al 1998a;Seguin et al 1998b), departures from Eq. 3 were observed at very high flow velocities.…”
Section: Introductionmentioning
confidence: 99%
“…3 does not apply at all flow velocities. In many studies (Fand et al 1987;Huang and Ayoub 2008;Seguin et al 1998a;Seguin et al 1998b), departures from Eq. 3 were observed at very high flow velocities.…”
Section: Introductionmentioning
confidence: 99%
“…If the reservoir is damaged, the damage mechanism should be taken into account when relating the non-Darcy skin to a b factor. For example, if the completion is damaged by an invading fluid, the derived b factor represents the altered rock rather than the uninvaded reservoir that is used to extrapolate back to the sandface, as assumed in the definition of skin (Van Everdingen 1953;Hawkins 1956;Hurst et al 1969).…”
Section: Resultsmentioning
confidence: 99%
“…Typically, the Forchheimer equation that considers both viscous and inertial impact is used to describe this phenomenon (Bear 1972). Recently, Barree and Conway (2004) and Huang and Ayoub (2008) showed that the b coefficient and Forchheimer equation have limitations, and proposed a new model with a plateau regime (Lai et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The viscous porous resistance tensor is determined by the horizontal and vertical permeability of the sediment. The equations of the CFD model are included in the supporting information section S1 of the paper (CD- ADAPCO, 2015;Huang & Ayoub, 2008;Jongen, 1992;Liu et al, 2012;Reynolds, 1894;Schmitt, 2007;Shih et al, 1995;Versteeg & Malaasekera, 1995;Wolfshtein, 1969).…”
Section: High-resolution Cfd Modelmentioning
confidence: 99%